Rockin' in the ivory tower rock music on campus in the sixties - Carter, James M. 1968- (Rutgers University Press, 2023)
"In Campus Rock, historian James M. Carter tells the story of the emergence of rock music culture in the U.S. during the late 1960s. The story places the college campus at the center of an emerging rock music circuit. As private clubs and other hosting venues did not exist and only slowly emerged, the performance of rock music thrived on campuses, where there already existed a built-in audience, a tradition of music performance, and a student body enjoying remarkable autonomy (and a budget) in planning activities. Of course, this did not occur in a vacuum, but was a key component of an array of related movements and phenomena that we have come to think of as "the sixties," including civil rights/free speech/anti-war movements, the counterculture, and the growth and spread of the underground press. Not simply coincidentally, rock music culture emerged simultaneous with, and as a part of, the counterculture. Campus Rock highlights how these multiple cultural, political, and social phenomena, often treated separately, were actually bound together and evolved in relation to each other in important ways"--
Keywords: Geschichte 1960-1971; Musikleben; Rockmusik; Rockkonzert; Campus; Universität; Hochschule; USA; Rock music / Social aspects / United States / History / 20th century; College campuses / Social aspects / United States / History / 20th century; Rock music / United States / 1961-1970 / History and criticism; Rock music; Rock music / Social aspects; United States; 1900-1999; Criticism, interpretation, etc; History